Comparison of Oral Melatonin and Midazolam as Premedication in Children Undergoing General Anesthesia for Dental Treatment - Faghihian, Reyhaneh (Anesth Pain Med, 2018)
BACKGROUND: Dental anxiety is prevalent in children. This condition may cause uncooperative behavior and need a treatment under general anesthesia. The perioperative period, especially for children, is a stressing event. Premedication is commonly used to reduce perioperative anxiety and facilitate the induction of anesthesia. METHODS: 132 children candidates for dental treatment under GA were enrolled in this study and randomly divided into 3 groups. Oral melatonin, midazolam, and normal saline were administered as premedication. Patient’s sedation score before GA, the ease of intravenous line establishment, patient’s need for painkillers, and duration of recovery were evaluated and compared. RESULTS: Regarding the sedation score and response to IV access establishment, comparisons showed statistically significant differences between melatonin and midazolam groups (P < 0.05) as well as between midazolam and placebo groups (P < 0.001). The difference between melatonin and placebo groups was not significant (P > 0.05). The need for painkiller administration was statistically different between midazolam and placebo, melatonin and placebo, and midazolam and melatonin groups (P < 0.05). A statistically significant difference was also found between melatonin and midazolam as well as between melatonin and placebo groups (P < 0.05) with regard to the recovery duration while no significant difference was observed between midazolam and placebo groups (P > 0.05). CONCLUSION: Midazolam is superior to melatonin for premedication regarding the patients’ sedation score before anesthesia and the ease of IV access establishment. Premedication with midazolam decreases the need for painkillers and increases the rate of recovery in children undergoing GA for dental treatment.